Arte e revelação do sagrado em Luigi Pareyson - Arcuri1, Isabella Guedes (Sacrilegens, 2010)
This article aims to present the artistic process as a possible opening to the sacred in the aesthetic theory of the Italian philosopher Luigi Pareyson. The artisticprocess is considered both in the formation of art work and in their contemplation. The painting "Black Square", the russian painter Kasemir Malevich ilustrates, as an example, this understanding.